Fibroblast growth factor blocks Sonic hedgehog signaling in neuronal precursors and tumor cells - Fogarty, Marie P. (National Academy of Sciences, 2007)
The Sonic hedgehog (Shh) and FGF signaling pathways regulate growth and differentiation in many regions of the nervous system, but interactions between these pathways have not been studied extensively. Here, we examine the relationship between Shh and FGF signaling in granule cell precursors (GCPs), which are the most abundant neural progenitors in the cerebellum and the putative cell of origin for the childhood brain tumor medulloblastoma. In these cells, Shh induces a potent proliferative response that is abolished by coincubation with basic FGF. FGF also inhibits transcription of Shh target genes and prevents activation of a Gli-responsive promoter in fibroblasts, which suggests that it blocks Shh signaling upstream of Gli-mediated transcription. FGF-mediated inhibition of Shh responses requires activation of FGF receptors and of ERK and JNK kinases, because it can be blocked by inhibitors of these enzymes. Finally, FGF promotes differentiation of GCPs in vitro and in vivo and halts proliferation of tumor cells from patched (ptc) mutant mice, a model for medulloblastoma. These findings suggest that FGF is a potent inhibitor of Shh signaling and may be a useful therapy for tumors involving activation of the hedgehog pathway.